1996
DOI: 10.1002/(sici)1096-8652(199609)53:1<1::aid-ajh1>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α-thalassemia trait on spleen function in sickle cell anemia patients with high HbF

Abstract: Spleen function was studied in a group of 20 Kuwaiti SS patients (aged 2-12 years), using 99mTc-labeled tin colloid scintigraphy. They were screened for the alpha-thalassemia determinants which are prevalent in the Arabian Peninsula [-alpha (3.7 kb) deletion, alpha2-globin gene polyadenylation signal (AATAAA => AATAAG) mutation, and 5' IVS-I splice junction pentanucleotide (GAGGTGAGG => GAGG) deletion] with a combination of polymerase chain reaction and allele-specific oligonucleotide (ASO) hybridization techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Since Hb F is uniformly high in our patients, it is not surprising that no correlation was found with TAMV. This is similar to our previous studies on avascular necrosis of the femoral head and spleen function in which no association was found with Hb F [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…Since Hb F is uniformly high in our patients, it is not surprising that no correlation was found with TAMV. This is similar to our previous studies on avascular necrosis of the femoral head and spleen function in which no association was found with Hb F [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…The other ameliorating factor in our patients is the high prevalence of ␣-thal trait, which was found in about 50% of the cases in the present study. Previous studies from our center showed that SS patients with co-inherited ␣-thal trait were more likely to retain good spleen function, have a reduced incidence of infections [23] and reduced prevalence of gallstones probably because of a less severe chronic hemolysis [24] when compared to SS patients with low Hb F levels.…”
Section: Discussionmentioning
confidence: 82%
“…This contributes significantly to the amelioration of the disease and protects the patients from many of its complications [23]. Overt stroke, chronic leg ulcers, priapism, acute chest syndrome, and early splenic dysfunction are uncommon [16,24,25]. However, a subset of patients exists who have frequent, severe painful crises, many of whom end up with osteonecrosis.…”
Section: Fig 1 Mri Of Brain (T2-weighted) Axial Section Showing Hypmentioning
confidence: 99%